The Effect Of Economic Growth On The Environmental Pressure Of Water Consumption In Algeria. Using Autoregressive Distributed Lag Analysis For The Period (1980-2019) - كديدة , آمال; بوختالة , سمير (khazzartech الاقتصاد الصناعي, 2021)
This paper aims to try to investigate the impact of economic growth on the environmental pressure of water consumption within the framework of the Kuznets environmental curve in Algeria, both in the short and long term, by conducting a formal study in Algeria during the period 1980-2019, The ARDL self-regression methodology was used to verify this study using variable the water consumption as a dependent variable and explanatory variables represented in real GDP and the population.. Based on the study variables, the study found that growth positively affects the environmental pressure of Algeria's water consumption in the short and long terms. This is different from the assumptions of Kuznets environmental curve.